Exosomes: Novel Biomarkers for Clinical Diagnosis - Jin Lin; Jing Li; Bo Huang; Jing Liu; Xin Chen; Xi-Min Chen; Yan-Mei Xu; Lin-Feng Huang; Xiao-Zhong Wang (The Scientific World Journal)
Exosomes are 30–120 nm endocytic membrane-derived vesicles that participate in cell-to-cell communication and protein and RNA delivery. Exosomes harbor a variety of proteins, nucleic acids, and lipids and are present in many and perhaps all bodily fluids. A significant body of literature has demonstrated that molecular constituents of exosomes, especially exosomal proteins and microRNAs (miRNAs), hold great promise as novel biomarkers for clinical diagnosis. In this minireview, we summarize recent advances in the research of exosomal biomarkers and their potential application in clinical diagnostics. We also provide a brief overview of the formation, function, and isolation of exosomes.